2021
DOI: 10.3390/s21206894
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Prediction Using Multivariate Time Series Deep Learning in the Lining of an Electric Arc Furnace for Ferronickel Production

Abstract: The analysis of data from sensors in structures subjected to extreme conditions such as the ones used in smelting processes is a great decision tool that allows knowing the behavior of the structure under different operational conditions. In this industry, the furnaces and the different elements are fully instrumented, including sensors to measure variables such as temperature, pressure, level, flow, power, electrode positions, among others. From the point of view of engineering and data analytics, this quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Discrete wavelet transform is more commonly used than continuous wavelet transforms for signal decomposition [29]. The Haar transformation is used in the noise reduction function because of its simplicity, versatility, and computational efficiency [30], as shown in (7) and (8).…”
Section: Wavelet Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrete wavelet transform is more commonly used than continuous wavelet transforms for signal decomposition [29]. The Haar transformation is used in the noise reduction function because of its simplicity, versatility, and computational efficiency [30], as shown in (7) and (8).…”
Section: Wavelet Transformmentioning
confidence: 99%
“…In fact, the process of implementing the Kalman filter is strongly depend on the system dynamic model which is set at the beginning and ineffective with the high variation data [7]. Another approach by Leon-Medina et al [8] using a deep neural network has also been carried out to minimize the amount of noise contained in the thermocouple data and obtain the best of root mean squared error (RMSE) value of 1.19 °C. However, the presence of noise is still visible in the peak signal area.…”
Section: Introductionmentioning
confidence: 99%
“…Through this approach, it was found that the carbon content had the largest effect on electrical energy consumption in the EAF. Leon–Medina et al [ 6 ] analyzed the voltage, power, and electrode positions of an EAF system and proposed an EAF temperature prediction model using a grated recurrent unit (GRU) deep learning model. Chen et al [ 7 ] applied a deep learning technique to energy consumption modeling to improve the energy efficiency of an EAF system.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…The lining monitoring variables comprise temperature, heat fluxes, water quality, remaining thickness refractory, sidewall erosion and protective layer formation, among others [14]. However, the development of temperature lining prediction models in an EAF is still an open research field because of the reduced number of works in this area [15,16].…”
Section: Introductionmentioning
confidence: 99%